PERAN PEJABAT PEMBUAT AKTA TANAH DALAM PEMBAUTAN AKTA TANAH DI INDONESIA - Faisal Bukhari; Nova Yarsina (Ensiklopedia of Journal, 2022)
Land Deed Maker Official, hereinafter referred to as PPAT, is a public official who is authorized to make a deed of transfer of land rights, deed of assignment of land rights, and deed of granting power of attorney to impose mortgage rights according to the applicable laws and regulations; b) Article 1 point 5 of Government Regulation Number 40 of 1996 concerning Cultivation Rights, Building Use Rights and Land Use Rights (hereinafter written PP Number 40 of 1996). Land Deed Making Official is a public official who is authorized to make land deeds; c) Article 1 number 24 of PP Number 24 of 1997. Land Deed Making Official, hereinafter referred to as PPAT, is a public official who is authorized to make certain land deeds; and d) Article 1 point 1 PP Number 37 of 1998. Land Deed Making Official, hereinafter referred to as PPAT, is a public official who is authorized to make authentic deeds regarding certain legal actions regarding land rights or Ownership Rights to Flat Units.Keywords: PPAT, Manufacture, Land Deed, Indonesia.